Famotidine, an Antiulcer Agent, Strongly Inhibits Helicobacter pylori and Human Carbonic Anhydrases - Angeli, Andrea (ACS Med Chem Lett, 2018)
[Image: see text] Famotidine, an antiulcer drug incorporating a sulfamide motif, was investigated as carbonic anhydrase inhibitor (CAI). It acts as a nanomolar inhibitor of several human (hCA II, VI, VII and XII) and Helicobacter pylori CAs. The high resolution X-ray structures of famotidine bound to hCA I and II revealed interesting aspects related to its CA inhibition mechanism, offering the possibility to develop antibacterials with a novel mechanism of action.